The Implementation of Talking Football Game Towards Students’ Speaking Skill at Second Semester English Department of STKIP Dharma Bakti Lubuk Alung - Amal Hayati; El Basthoh; Kodirova Dilnoza Murtazaevna (Bulletin of Pedagogical Research, 2021)
The purpose of this research was to know the students’ speaking ability by implementing Talking Football Game at second semester English Department students of STKIP Dharma Bakti Lubuk Alung. This research was experimental research called One-Shot Case Study which used one class as the sample. The population of this research was second semester English Department students of STKIP Dharma Bakti Lubuk Alung registering in 2014-2015 Academic Year. The data of this research were collected by using oral test. The data were analyzed by t-test formula. From the calculation of the result of the test, it was indicated that tcalculate was 3, 22 and ttable 2, 02 with a = 0,05. So, it means that tcalculate was greater than ttable and the hypothesis was accepted. The result of this research showed that Talking Football Game increase students’ speaking ability. It implied that Talking Football Game could be used as a technique of teaching speaking ability at second semester English Department students of STKIP Dharma Bakti Lubuk Alung year of 2014-2015. Keywords: Talking Footbal Game, Speaking Skill, Speaking Ability